PENGARUH KINERJA KEUANGAN DAN KEPEMILIKAN MANAJERIAL TERHADAP FINANCIAL DISTRESS (Media Riset Akuntansi, 2022)
This study aims to analyze the effect of liquidity, profitability, leverage, managerial ownership on financial distress manufacturing companies listed on the Indonesia Stock Exchange. This study uses four independent variables namely liquidity, profitability, leverage, managerial ownership. While the dependent variable in this study is financial distress. This study uses a sample of manufacturing companies listed on the Indonesia Stock Exchange during the period 2015-2017. The source of data in this study is to use secondary data. Purposive sampling is used as a sampling method and obtained as many as 78 samples over a period of three years. The analytical tool used is logistic regression analysis. The results showed that liquidity affected financial distress, while profitability, leverage, managerial ownership did not affect financial distress.